Political Myths in Plato and Asimov - Nathaniel Goldberg (Journal of Science Fiction and Philosophy, 2019)
Works of science fiction tend to describe hypothetical futures, or counterfactual pasts or presents, to entertain their readers. Philosophical thought experiments tend to describe counterfactual situations to test their readers’ philosophical intuitions. Indeed, works of science fiction can sometimes be read as containing thought experiments. I compare one especially famous thought experiment from Plato’s Republic with what I read as two thought experiments from Isaac Asimov’s Foundation Trilogy. All three thought experiments concern myths used in political contexts, and comparing them permits me to analyze the morality of political mythologizing.